Body temperature of the parasitic wasp Pimpla turionellae (Hymenoptera) during host location by vibrational sounding - KRODER, STEFAN (2008)
The pupal parasitoid Pimpla turionellae (L.) uses self-produced vibrations transmitted on the plant substrate, so-called vibrational sounding, to locate immobile concealed pupal hosts. The wasps are able to use vibrational sounding reliably over a broad range of ambient temperatures and even show an increased signal frequency and intensity at low temperatures. The present study investigates how control of body temperature in the wasps by endothermic mechanisms may facilitate host location under changing thermal environments. Insect body temperature is measured with real-time IR thermography on plant-stem models at temperature treatments of 10, 18, 26 and 30 °C, whereas behaviour is recorded with respect to vibrational host location. The results reveal a low-level endothermy that likely interferes with vibrational sound production because it occurs only in nonsearching females. At the lowest temperature of 10 °C, the thoracic temperature is 1.15 °C warmer than the ambient surface temperature whereas, at the high temperatures of 26 and 30 ° C, the wasps cool down their thorax by 0.29 and 0.47 °C, respectively, and their head by 0.45 and 0.61 °C below ambient surface temperature. By contrast, regardless of ambient temperature, searching females always have a slightly elevated body temperature of at most 0.30 °C above the ambient surface temperature. Behavioural observations indicate that searching females interrupt host location more frequently at suboptimal temperatures, presumably due to the requirements of thermoregulation. It is assumed that both mechanisms, producing vibrations for host location and low-level endothermy, are located in the thorax. Endothermy by thoracic muscle work probably disturbs signal structure of vibrational sounding, so the processes cannot be used at the same time.